Revering Water Learning from Intelligent Traditional Systems (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
Water always has been one of the most fundamental resource for all civilizations, especially for human consumption. Yet, it is the most critical resource in contemporary times with an unfortunate situation of both, widespread lack of water and widespread lack of respect for remaining available water. The situation would come across as quite the contrary, if explored are bygone times, especially in historically rich civilizations of India. Traditional wisdom always respected water and developed intelligent inter-relationship with nature, people, culture and architecture. A symbiotic design language of built environment, incorporating design creativity and scientific reasonings, was discernible and efforts to stimulate respect for water was evident. Traditional knowledge systems for water resources, covered a broad spectrum of built environment - from settlements to built form, from macro level layouts to micro level detailing. Regrettably, the contemporary design processes have disrespected water resources, related traditional systems and the reinforcing cultural ethos. At the same time, understanding the intelligent traditional systems and their contextual essence could facilitate an effective synergy with the contemporary situations. Public participation in the design process could become the underlying current for reviving respect for water. They could be rediscovered, reinvented and integrated into the contemporary design processes.